Educational Arrangements Toward Human Capital Development: Evidence from the Malaysian and Jordanian Universities - Ishaq Ibrahim; Ali Nasser Altahitah; Wesam Almahallawi; Kalsom Ali; Ihab Ahmed Ra'Uf Awais; Abdul Rashid Abdul Aziz (Elsevier, 2024)
Non-Indexed Publication